Popular participation and urban development policy in Cruz de Motupe - Ticllacuri Meza, Hoffmann (2020)
The complexity of the social infrastructure projects has been the expression of an unfinished development, as is the case of the construction of tracks and sidewalks in the young town of Cruz de Motupe during 2011. The objective of the research seeks to explore the development of the participation of the popular sector in the management of public works policies under the shadow of a pattern of municipal power that has been articulated within the state apparatus. The methodology has been carried out by accessing the statutes, photos and public investment documents from the Municipality of San Juan de Lurigancho and the Integral Program for the Improvement of Neighborhoods and Towns (PIMBP) of the Ministry of Housing, Construction and Sanitation.